Early Cretaceous back‐arc basin basalt‐type gabbros in the southeastern Tibetan Plateau: Implications for Neo‐Tethyan oceanic slab subduction. Issue 5 (6th February 2022) - Xie, Zhipeng; Xue, Chuandong; Yang, Tiannan; Wang, Wei; Liu, Jingkun; Xin, Di
Abstract : Although progress has been made in defining and explaining the temporal and spatial distributions of Neo‐Tethyan magmatism in the Tibet–Himalaya region, the correlation of magmatic suites in the SE Tibetan Plateau remains poorly constrained. This paper reports zircon U–Pb dating, geochemistry, and Sr–Nd isotope compositions of a concealed gabbroic unit (coverage area of >6.0 km 2 ) in the southern Lancangjiang tectonic zone, western Yunnan, SW China. Zircon 206 Pb/ 238 U ages of 143–133 Ma indicate that the unit formed during the Early Cretaceous (ca. 139.7 Ma). The gabbro samples have variable MgO (7.88–16.1 wt%; Mg # = 58–74) and relatively low TiO2 (0.76–1.24 wt%) and total‐alkali (K2 O + Na2 O = 2.61–4.06 wt%) contents. The samples exhibit weakly fractionated rare earth element (REE) patterns with slight depletion in light REEs and negligible Eu anomalies. In a primitive‐mantle‐normalized element‐variation diagram, the gabbros, display variable enrichment in large‐ion lithophile elements and relatively flat patterns of high‐field‐strength elements. Initial 87 Sr/ 86 Sr ratios of 0.7079 to 0.7142 and relatively depleted ε Nd ( t ) values of +3.96 to +4.84 are similar to those of the mantle source of back‐arc basin basalts (BABBs) in the central Lhasa Block and mid‐ocean ridge basalt in the Indus–Tsangpo Suture Zone. These various characteristics suggest that the gabbroic unit was derived from a shallow and depleted mantle source by relatively high‐degree partial melting in the spinel stability field. The parental magma underwent slight crustal contamination, as well as fractional crystallization of clinopyroxene. The studied gabbros have distinct BABB‐type geochemical affinities similar to those of the Okinawa BABB. Combining our data with the coeval occurrence of a continental rift basin (the Simao–Lanping Basin) leads us to suggest the existence of a back‐arc rifting setting in the SE Tibetan Plateau during the Jurassic–Cretaceous. This setting can also be geochronologically and genetically correlated to the back‐arc basin developed within the Lhasa Block. These settings and constituent characteristics formed as a result of Neo‐Tethyan oceanic slab subduction during the late Mesozoic. Abstract : A concealed Early Cretaceous gabbroic unit is identified in the SE Tibetan Plateau. The gabbros originated from high‐degree partial melting of a depleted mantle source. The gabbros have similar geochemistry to that of typical back‐arc basin basalt. The gabbroic unit formed in a back‐arc rifting environment. Results reveal subduction of the Neo‐Tethyan oceanic slab beneath the Sibumasu Block.